Penerapan Model Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas VIII1 SMPN 6 Siak Hulu - Enno Triandini,; Heleni, Susda; Saragih, Sehatta (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This research is motivated by the low mathematics achievement of the eighth-grade students of SMPN 6 Siak Hulu in the academic year 2023/2024. This study aims to improve the quality of the learning process and mathematics learning outcomes by implementing the Problem-Based Learning (PBL) model. The form of this research is Classroom Action Research, which examines the problems faced and takes action to solve them. The subjects of this research consist of the eighth-grade students of SMPN 6 Siak Hulu in the odd semester of the academic year 2023/2024, comprising 15 male students and 12 female students with diverse abilities. Research instruments involve using syllabi, Lesson Implementation Plans (RPP), and Student Worksheets (LKS) as learning aids. Meanwhile, observation sheets and learning outcome tests are data collection instruments. The results show an improvement in the learning process from the initial score to each cycle, as reflected in students' increased mathematics learning achievement. The improvement in the Minimum Completion Criteria (KKM) results is as follows: in terms of knowledge and skills, it increased from 11 students (40.7%) in cycle I to 14 students (51.8%) in cycle II. It reached 17 students (62.9%) in cycle III. This research concludes that the implementation of the Problem-Based Learning (PBL) model successfully improves the learning process and achieves better mathematics learning outcomes for the eighth-grade students of SMPN 6 Siak Hulu in the academic year 2023/2024, particularly in the topic of System of Linear Equations with Two Variables.